Safety and efficacy of feed additives obtained from the fruit of Pimpinella anisum L.: anise oil for use in poultry and horses and anise tincture for use in poultry, dogs, cats and horses (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of anise oil and anise tincture obtained from the fruit of Pimpinella anisum L., when used as sensory additives. The use of the anise oil at the proposed use level in complete feed of 1.9 mg/kg for laying hens and 5 mg/kg for horses was considered very unlikely to induce adverse effects. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) had no safety concern when anise oil is used at the proposed use levels of 1.5 mg/kg for chickens for fattening and at 1.7 mg/kg for turkeys for fattening. The use of anise tincture at the proposed conditions of use in dogs, cats, horses and laying hens was considered very unlikely to induce adverse effects, and of no concern in chickens for fattening. The use of the additives in animal feed is expected to be of no concern for consumers. The additives under assessment should be considered as irritants to skin and eyes, and as dermal and respiratory sensitisers. Due to the high concentration of estragole (≥ 1%), anise oil is classified as suspected of causing genetic defects and of causing cancer and should be handled accordingly. When handling anise tincture, exposure of unprotected users to estragole may occur. Therefore, to reduce the risk, the exposure of the users should be minimised. The use of these additives in animal feed was not expected to pose a risk to the environment. Since the fruit of P. anisum and its preparations are recognised to flavour food and their function in feed would be the same, no further demonstration of efficacy was considered necessary.